2017
DOI: 10.15171/mejdd.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Gastroesophageal Reflux Disease in Southern Iran: Pars Cohort Study

Abstract: BACKGROUND Prevalence of gastroesophageal reflux disease (GERD) is increasing worldwide. We aimed to estimate the prevalence of GERD in Pars Cohort Study (PCS) and to find its correlates. METHODS We used the baseline data from PCS. PCS was conducted in the district of Valashahr in Fars province in southern Iran from 2012 to 2014. 9264 inhabitants who were 40-75 years old, and agreed to participate were enrolled. Data were collected by a structured questionnaire and simple physical examination of all participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…For example, the prevalence of GERD in Iranian general population is reported from a minimum of 2.8%, 32 to a maximum of 58.5%. 33 Based on the better methodology, in a large cohort study with 50,000 participants in the North of Iran a representative prevalence rate of 20% has been estimated. 13 A systematic review has also reported the prevalence rate of 21.2% in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the prevalence of GERD in Iranian general population is reported from a minimum of 2.8%, 32 to a maximum of 58.5%. 33 Based on the better methodology, in a large cohort study with 50,000 participants in the North of Iran a representative prevalence rate of 20% has been estimated. 13 A systematic review has also reported the prevalence rate of 21.2% in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…We also included severe gastroesophageal reflux disease, irritable bowel syndrome, and functional constipation based on clinical criteria presented elsewhere. [19][20][21] Participants were classified into three categories, without chronic disease, with one or two chronic diseases, and with more than two chronic conditions (multi-morbidity).…”
Section: Possible Correlatesmentioning
confidence: 99%